Complete hepatitis B virus prophylaxis withdrawal in hepatitis B surface antigen–positive liver transplant recipients after longterm minimal immunosuppression. Issue 9 (1st August 2016) - Lenci, Ilaria; Baiocchi, Leonardo; Tariciotti, Laura; Di Paolo, Daniele; Milana, Martina; Santopaolo, Francesco; Manzia, Tommaso Maria; Toti, Luca; Svicher, Valentina; Tisone, Giuseppe; Perno, Carlo Federico; Angelico, Mario
Abstract : Tailored approaches have been attempted to prevent hepatitis B virus (HBV) reinfection in antibodies against hepatitis B surface antigen (HBsAg)–positive liver transplantation (LT) recipients in order to minimize the use of hepatitis B immune globulin (HBIG) and nucleoside analogues (NAs). We report the results of complete HBV prophylaxis withdrawal after a follow‐up of at least 6 years in LT recipients with undetectable serum HBV DNA and intrahepatic total HBV DNA and covalently closed circular DNA at LT. We included 30 HBsAg positive, hepatitis B e antigen–negative recipients, 6 with hepatitis C virus and 7 with hepatitis D virus coinfection, who had received HBIG plus NA for at least 5 years after LT. Stepwise HBIG and NA withdrawal was performed in two 6‐month periods under strict monitoring of HBV virology. All patients underwent a clinical, biochemical, and virological follow‐up at 3‐6 month intervals. HBV recurrence (HBsAg seroreversion ± detectable HBV DNA) occurred in 6 patients: in 1 patient after HBIG interruption and in 5 after both HBIG and NA cessation. Only 3 patients required reinstitution of HBV prophylaxis because of persistent HBV replication, and all achieved optimal control of HBV infection and did not experience clinical events. The other who recurred showed only short‐lasting HBsAg positivity, with undetectable HBV DNA, followed by spontaneous anti‐HBs seroconversion. An additional 15 patients mounted an anti‐HBs titer, without previous serum HBsAg detectability. At the end of follow‐up, 90% of patients were still prophylaxis‐free, 93.3% were HBsAg negative, and 100% were HBV DNA negative; 60% had anti‐HBs titers >10 IU/L (median, 143; range, 13‐1000). This small series shows that complete prophylaxis withdrawal is safe in patients transplanted for HBV‐related disease at low risk of recurrence and is often followed by spontaneous anti‐HBs seroconversion. Further studies are needed to confirm this finding. Liver Transplantation 22 1205–1213 2016 AASLD